2017
DOI: 10.1007/s10787-017-0358-8
|View full text |Cite
|
Sign up to set email alerts
|

Class side effects: decreased pressure in the lower oesophageal and the pyloric sphincters after the administration of dopamine antagonists, neuroleptics, anti-emetics, l-NAME, pentadecapeptide BPC 157 and l-arginine

Abstract: The ulcerogenic potential of dopamine antagonists and L-NAME in rats provides unresolved issues of anti-emetic neuroleptic application in both patients and experimental studies. Therefore, in a 1-week study, we examined the pressures within the lower oesophageal and the pyloric sphincters in rats [assessed manometrically (cm HO)] after dopamine neuroleptics/prokinetics, L-NAME, L-arginine and stable gastric pentadecapeptide BPC 157 were administered alone and/or in combination. Medication (/kg) was given once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(98 citation statements)
references
References 57 publications
2
96
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] BPC 157 also acts as a free radical scavenger, counteracts free radical-induced lesions, and normalizes NO and MDA levels in tissues and during ischemia and reperfusion. 101,113,114,[116][117][118] Subsequent studies from other groups 2,96-101 have confirmed our original findings. [65][66][67][68][69][70][71][72][73][74][75][76][77][78] Pleotropic effects involving distinctive receptors, including VEGFR2 and growth hormone receptors, distinctive pathways, including VEGFR2-AKT-eNOS, ERK ½, FAK-paxillin, FoxO3a, p-AKT, p-mTOR and p-GSK-3β, and distinctive loops, including stimulation of the egr-1 gene and its corepressor gene naB2, and counteraction of increases in pro-inflammatory and procachectic cytokines, 2,[96][97][98][99][100][101] likely minimize the inherent lack of full understanding of the mechanisms that may be involved.…”
Section: Homeostasissupporting
confidence: 81%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] BPC 157 also acts as a free radical scavenger, counteracts free radical-induced lesions, and normalizes NO and MDA levels in tissues and during ischemia and reperfusion. 101,113,114,[116][117][118] Subsequent studies from other groups 2,96-101 have confirmed our original findings. [65][66][67][68][69][70][71][72][73][74][75][76][77][78] Pleotropic effects involving distinctive receptors, including VEGFR2 and growth hormone receptors, distinctive pathways, including VEGFR2-AKT-eNOS, ERK ½, FAK-paxillin, FoxO3a, p-AKT, p-mTOR and p-GSK-3β, and distinctive loops, including stimulation of the egr-1 gene and its corepressor gene naB2, and counteraction of increases in pro-inflammatory and procachectic cytokines, 2,[96][97][98][99][100][101] likely minimize the inherent lack of full understanding of the mechanisms that may be involved.…”
Section: Homeostasissupporting
confidence: 81%
“…41,114 The notation that BPC 157-NOsystem-relation interferes with the effects of neuroleptics merits further elaboration. 115,116 Finally, BPC 157 application lead to normalization of NO-level in tissues as well as counteraction of free-radicals formation. 113,114,116 Of note, how this advantage of modulating NO-system (i.e., particular effect on eNOS gene), may be a practical background which could be further translated into an enhanced clinical performance.…”
Section: Bpc 157 Stomach Cytoprotection Concept → Wound Heal-mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the antioxidant system may play an essential role during midgut invasion, which is however, largely disabled in invaded honeybees (Dussaubat et al, 2012). Thus, although this was not specifically investigated in insect midgut, it should be noted that various free radicals-induced lesions in other organs were also counteracted by BPC 157 administration (Ilic et al, 2010;Luetic et al, 2017;, and in particular, ischemia/reperfusion injuries in rat colitis (Duzel et al, 2017). Thus, it was suggested that BPC 157 may serve as a possible antioxidant (i.e., BPC 157 contains four carboxylic groups, all of them could be active in scavenger process and if reactivated [e.g., by glutathione or by enzymes], the overall beneficial activity could be very high; Duzel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this effect may be the cause or a consequence of the beneficial effects of BPC 157 on related disturbances [1][2][3][4][5][6][7][8][9][10][11]. As demonstrated, BPC 157 counteracts free radical formation and free radical-induced lesions [32,[82][83][84]. An interesting point would be the use of the same dose range in BPC 157 studies [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 94%